2018
DOI: 10.1186/s12887-018-1208-6
|View full text |Cite
|
Sign up to set email alerts
|

The CANadian Pediatric Weight management Registry (CANPWR): lessons learned from developing and initiating a national, multi-centre study embedded in pediatric clinical practice

Abstract: BackgroundThere is increasing recognition of the value of “real-world evidence” in evaluating health care services. Registry-based, observational studies conducted in clinical settings represent a relevant model to achieve this directive. Starting in 2010, we undertook a longitudinal, observational study (the CANadian Pediatric Weight management Registry [CANPWR]), which is embedded in 10 multidisciplinary, pediatric weight management clinics across Canada. The objective of this paper was to share the lessons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Their quantitative data revealed that attrition was higher in older children (≥12 years old) and among families receiving social assistance; qualitative data indicated common reasons for attrition included logistical barriers and interventions not meeting families' needs (eg, families disagreed with the treatment focus or intervention length). Initial data from the CANadian Pediatric Weight management Registry (CANPWR), an ongoing study of children enrolled in multi‐disciplinary obesity management, 23 showed that attrition often occurs early in treatment 24 . Other reports showed that predictors of attrition differed depending on when attrition occurred (ie, earlier vs later in treatment) 25,26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their quantitative data revealed that attrition was higher in older children (≥12 years old) and among families receiving social assistance; qualitative data indicated common reasons for attrition included logistical barriers and interventions not meeting families' needs (eg, families disagreed with the treatment focus or intervention length). Initial data from the CANadian Pediatric Weight management Registry (CANPWR), an ongoing study of children enrolled in multi‐disciplinary obesity management, 23 showed that attrition often occurs early in treatment 24 . Other reports showed that predictors of attrition differed depending on when attrition occurred (ie, earlier vs later in treatment) 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…Initial data from the CANadian Pediatric Weight management Registry (CANPWR), an ongoing study of children enrolled in multi-disciplinary obesity management, 23 showed that attrition often occurs early in treatment. 24 Other reports showed that predictors of attrition differed depending on when attrition occurred (ie, earlier vs later in treatment). 25,26 For instance, Spence et al 25 showed that higher self-assessed health of the family system was associated with lower short-term attrition (ie, up to 4-months post-baseline) whereas higher percentage of intervention sessions attended by parents was associated with lower long-term attrition (ie, from 4-to 12-months postbaseline).…”
mentioning
confidence: 99%
“…Many HCMS and some clinicians highlighted the need to embed research into clinical practice to inform best practice models of care and enable the development of a business case for new and/or expansion of services. Clinical groups in Europe (Kurth et al, 2008), Canada (Morrison et al, 2018) and the United States of America (Kirk et al, 2017) have developed central registries to record and analyze standard clinical outcome data from multiple sites in each country. These central registries enable the development of high-quality and meaningful outcome data and multi-site research to identify best practices for pediatric weight management (Kirk et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The major limitation of DREPADO trial is the difficulty to implement the transition programme because the intervention is complex [23]; it involves different departments of care, different places of intervention (home, hospital, "neutral place"), and different types of expertise (or the training of personnel in several different fields). This complexity requires good communication and coordination between interlocutors; to aid in this regard, the DREPADO study group provides to each centre tools for communication and training.…”
Section: Discussionmentioning
confidence: 99%